Tourists’ Safety in the Risk Society: Explaining Perceptions of Safety Regarding Future Vacations - Mawby, Rob (International criminal justice review, 2024)
While the risk of crime and perceptions of safety have been regularly addressed by criminologists, this has rarely extended to asking how those considering or taking vacations perceive their security. In contrast, tourism researchers regularly focus on perceptions of safety but define this more broadly to include, inter alia, safety from health risks and natural disasters. This paper melds the two disciplines by considering which destinations US residents perceived as unsafe, focusing on risks from crime, political unrest or terrorism, and health concerns. The research used a crowdsourcing platform to collect citizens’ perceptions of safety with regard to crime, terrorism/political disorder, and health problems at the height of the COVID-19 pandemic. The findings suggest that health problems were seen as the greatest risk, but not excessively so. Mexico and China were seen as the most risky countries to visit, although US residents also considered the USA a relatively dangerous place to spend a vacation. Variations in perceptions of safety between subgroups of respondents were greatest for health problems and least for crime, suggesting that fear of crime is associated with features of everyday life that are less relevant to tourism destinations. The paper concludes by discussing the relevance of the findings for both the tourism sector and criminology.